Incidence of the anisotropy in the detraction of water of a lentic or lotic system by anthropic actions, determined through numeric modeling - Aristizábal Rodríguez, Héctor Fabio; Escobar Chalarca, Carlos Alberto; Martínez Santos, Pedro (Revista Colombiana de Investigaciones Agroindustriales, 2015)
To estimate the amount of water subtracted wetlands and rivers (lentic and lotic systems) produced by the use of groundwater, there are analytical methodologies that include the hypothesis of the isotropy of the medium in the XY plane, limited to particular conditions. Currently, numerical models allow considering scenarios of large and complex simulation. This research aims to determine the importance of including the anisotropy of the medium in this anthropic process. The implementation was done on grounds of Haciendas Ginebra and San Felipe in the municipality of Tulua, Valle del Cauca, Colombia and modeled with the mudflow package RIVER tool. The results show the existence of anisotropy values for hydraulic conductivity Kx = 1.9 m / day and Ky = 0.75 m / day. We conclude that the anisotropy directly influences the estimate and suggests inclusion in similar analyzes to ensure environmental sustainability of the system. Para citar este artículo Aristizábal, H., Escobar, C. y Martínez, P. (2015). Incidencia de la Anisotropía en la detracción de agua de un sistema léntico o lótico por acciones antrópicas, determinada mediante modelación numérica. Rev. Colomb. Investig. Agroindustriales, 2(1), 53-60. DOI: http://dx.doi.org/10.23850/24220582.169